Solar energy as alternative energy in a household - Mamontov, R. (ТДАТУ, 2018)
Normal life of a modern civilization is impossible without electric energy. Therefore ensuring high reliability of electrical supplies, its rational use, the maximum reduction of expenses in the course of its production, transfer and distribution are very important. Today, the use of electrical energy has reached large volumes, and the price of electricity rises every year. The question of using alternative energy sources arises.
Keywords: electricity; energy sources; material goods; environmental situation